Perbandingan Sistem Ekonomi dan Ciri Utama Ekonomi Syari’ah - Maryam Batubara; Andrian Syahputra; Azra Afwandy; Evan Hamdani (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2023)
This research aims to provide in-depth knowledge about the fundamental differences between conventional economic systems and the characteristics of sharia economics. This research methodology is a literature review research which provides output to existing data. This research data has implications for the direction of society and the economy as a whole. Based on the conclusions of this research, the fundamental difference between conventional economics and Islamic economics lies in the view of rationality, economic goals, emphasis on needs, and consumer and producer orientation. In Islamic economics, it is important to achieve holistic balance in the material and spiritual groups to obtain prosperity on earth and in the afterlife